Using Animated Shorts to Improve Narrative Writing Skills in Students You said:: Menggunakan Film Animasi Pendek untuk Meningkatkan Keterampilan Menulis Naratif Siswa - Hanifah, Nurul; Taufiq, Wahyu (Universitas Muhammadiyah Sidoarjo, 2024)
General Background: The integration of multimedia resources in education has gained attention for its potential to enhance student engagement and learning outcomes. Specific Background: While various teaching methods exist, the role of animated short movies in developing narrative writing skills among junior high school students remains underexplored. Knowledge Gap: Previous research has primarily focused on traditional methods of writing instruction, leaving a gap in understanding the specific effects of visual storytelling on writing proficiency. Aims: This study investigates the use of animated short movies as a tool for teaching narrative text writing skills to ninth-grade students in a junior high school in Sidoarjo, Indonesia. Results: A pre-test was administered to assess students’ initial writing skills, followed by a treatment using animated short movies, culminating in a post-test. The results indicated a significant increase in mean scores from 76.87 (pre-test) to 89.06 (post-test), supported by t-test analysis demonstrating improved writing quality. Novelty: This study contributes new insights into effective teaching strategies by highlighting the positive role of animated short movies in narrative writing instruction. Implications: The findings suggest that educators can incorporate animated short movies to create a more engaging and enjoyable writing learning environment, potentially leading to better student outcomes in narrative text composition. Highlights: Significant Improvement: Students’ narrative writing scores increased from 76.87 to 89.06 after using animated short movies. Engaging Learning Tool: Animated short movies effectively enhance student engagement in writing instruction. Effective Teaching Strategy: Incorporating multimedia resources can lead to improved learning outcomes in narrative writing. Keywords: animated short movies, narrative writing, junior high school, student engagement, teaching strategy.